The influence of celebrity endorsement and instagram ads feature on instagram to increase online customer’s purchase intention towards natural ingredients based cosmetic brand - Kusumaningrum, Andriaty; Chaerudin, Rendra (Journal of Innovation, Business and Entrepreneurship, 2019)
In Indonesia, Instagram become one of four application that most likely to be used with an increasing number of active users up to 1 billion in 2019 globally, Instagram’s growth eventually creates business opportunities because the amount of potential market gathered in one platform. With the goal of the endorsement done by small and medium enterprises to advance the promotion of their items and brand, celebgram has turned into a pattern among people in general, and their well-known can be same with other celebrities by only utilizing Instagram. Instagram Ads is a strategy for paying to post supported substance on the Instagram stage to come to a bigger and more focused on group of onlookers. Purchase intention has another perspective that the customer will buy an item after assessment. is affected by various factors such as price of the product, design, packaging, knowledge about the product, quality, celebrity endorsement, fashion and sometimes family relation as well. These connection between Celebrity Endorsement, Instagram Ads and purchase intention helps Small and Medium Enterprises to utilize Instagram as one of their marketing platform. The purpose of this study is to determine the effectiveness of marketing process using Celebrity Endorsement and instagram Ads as the tool. This research is expected to be useful and can be implemented for Small Medium Enterprise specifically for Naturale Indonesia also natural ingredients based cosmetic industry. This research used quantitative method by using probability sampling, data collection technique using Slovin formula with error of 10% and get 100 sample respondents. The analysis used is multiple linear regression to test the hypothesis. The results of this study indicates that both Celebrity Endorsement and InstagramAds has positive impact to increase customer’s purchase intention towards natural ingredients based cosmetic.\Keywords: Celebrity Endorsement, Instagram Ads, Natural Ingredients Based Cosmetic, Purchase Intention